ARTERIAL HYPERTENSION IN SYSTEMIC VASCULITIS: CLINICAL FEATURES AND PRINCIPLES OF PATHOGENETIC THERAPY. PART II. POSSIBILITIES OF OPTIMIZING OF ANTIHYPERTENSIVE TREATMENT - E. A. Praskurnichy; N. G. Poteshkina (Рациональная фармакотерапия в кардиологии, 2015)
The article deals with the problem of arterial hypertension in systemic vasculitis. Data on the principles of antihypertensive treatment of systemic vasculitis are presented. The possibilities of pharmacotherapy and surgical treatment of these diseases are discussed separately.